Fatigue Analysis for Void Repair of Cement Concrete Pavement with Under Slab by Polymer Grouting - Can Cui; Chengchao Guo; Fuming Wang (Civil Engineering Journal, 2019)
After the appearing of voids beneath cement concrete slabs, the pavement loses a continuous and uniform lower support structure, and the stress state of the road panel is extremely unfavorable. The polymer grouting repair is timesaving, efficient and pollution-free. In order to verify the performance improvement and fatigue damage evolution of cement concrete pavement before and after grouting repair, a material damage constitutive model was established. The UMAT subprogram was introduced into the finite element software ABAQUS to analyze the structure under the action of moving cyclic loading, stress response and fatigue damage evolution process before and after regional grouting repair. The results show that the Mises stress and vertical displacement of the grouting repairing slab are very close to the normal state, which indicates that the grouting repair has a prominent influence on the bottom void of the slab. With the rise of loading time, the fatigue damage of the pavement structure is increasing, but the trend is gradually reduced, and the number of load times and the degree of fatigue damage are nonlinear. From the long-term cyclic loading and comprehensive analysis of the construction period, the polymer grouting repair is better than cementitious grout.